PENDIDIKAN BAGI ANAK DI LEMBAGA PEMASYARAKATAN KHUSUS ANAK KELAS IIA JAKARTA - Firman Assiddiqi (Universitas Negeri Medan, 2020)
In the implementation of education for children organized by the Special Correctional Institution of class II A Jakarta, children have learned or educated education, formal, informal, and informally. In this study the approach used by the authors is a qualitative approach, wherein in this research the author does how a series of interviews, observations and literature research to acquire data, in this research author Also uses a descriptive research method in which to describe the existing problems of education for children. At A grade II children's prison in Jakarta, education is not only based on formal education, other education is also held as well as non-formal and informal education. This informal education in the form of education is pursuing a package for those correctional students who have not completed their education by the time they have not been caught by the case of criminal acts, informal education provided to the child by the officer is Spiritual education and skills. As for the barriers to the education process, there are two barriers that are internal barriers posed from within each child and external obstacles caused by outside factors such as officers and environment. The implementation or granting of educational rights in the class prison of IIA Jakarata still does not match what is expected.Keywords: Education, children, Correctional Special for Children